ラプテフカイ レナガワ リュウイキ ニ オケル スイモンガク チョウサ ケンキュウ ノ ヨサツ ホウコク - 伊藤, 一; イトウ, ハジメ; Ito, Hajime (2000)
P(論文) 1999年7・8月にロシア国レナ川流域およびラプテフ海において, 地球規模水循環の観点から北極海大陸棚での海氷生成を含めた水文学研究計画の準備的調査を実施した。調査結果を報告する。 A preparatory field investigation was carried out in July and August 1999 in the Lena basin and in the Laptev Sea, Russia. The hydrology of the region including the sea ice on the continental shelf is an important element in the global water circulation. The results of the work are reported. departmental bulletin paper